2022
DOI: 10.1002/cncr.34442
|View full text |Cite
|
Sign up to set email alerts
|

Screening brain MRI in inflammatory breast cancer: Is it time?

Abstract: The study of brain metastasis (BrM) in patients with inflammatory breast cancer (IBC) by Warren et al. that accompanies this editorial has reported a high incidence of BrM and poor survival after BrM diagnosis. The question rises: should we adopt routine brain MRI in patients with IBC for early detection of BrMs and will this make a difference in survival and quality of life of patients? This editorial tries to approach these questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The development of brain metastasis, as observed in this patient, significantly affects the prognosis. A study reported that the incidence of brain metastasis among patients with stage III inflammatory breast cancer was 5%, 9%, and 18%, with triple-negative breast cancer having the worst overall survival (0.2 years) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The development of brain metastasis, as observed in this patient, significantly affects the prognosis. A study reported that the incidence of brain metastasis among patients with stage III inflammatory breast cancer was 5%, 9%, and 18%, with triple-negative breast cancer having the worst overall survival (0.2 years) [16].…”
Section: Discussionmentioning
confidence: 99%